2016
DOI: 10.1055/s-0042-101941
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel through-the-needle biopsy forceps in endoscopic ultrasound

Abstract: Background and aims: Pancreatic cysts are becoming more common. Their differential diagnosis includes benign, premalignant, and malignant lesions. Distinguishing the type of cyst helps in the management decision making. We report on a novel tissue acquisition device for pancreatic cysts. Methods: Data on two patients who underwent endoscopic ultrasound (EUS) – guided fine-needle aspiration with a new micro forceps device are presented. Results: Two patients had large pancreatic cystic lesions in the pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…Since 2010, several case reports using different micro‐forceps working through a 19‐gauge EUS needle, and a recently published, small, single‐center, retrospective study, have shown encouraging results on the possibility of sampling of PCL cystic walls.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, several case reports using different micro‐forceps working through a 19‐gauge EUS needle, and a recently published, small, single‐center, retrospective study, have shown encouraging results on the possibility of sampling of PCL cystic walls.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported the utility of EUS‐through‐the‐needle biopsy (EUS‐TTNB) for the diagnosis and risk stratification of the malignancy of pancreatic cystic lesions . This novel technique enables direct sampling from the walls of pancreatic cystic lesions using biopsy microforceps through an EUS‐FNA needle.…”
Section: Methodsmentioning
confidence: 99%
“…Other applications for 19‐G needles are represented by the insertion of miniaturized devices, such as confocal microscopy fiberoptic probe or biopsy forceps for the diagnosis of cystic pancreatic lesions …”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 99%